Underdog or Top Dog Brand Story? The Role of Self-Construal and Need of Uniqueness - Li, Yalin; Zhao, Min (Frontiers in Psychology, 2021)
How to design an effective brand story has become a key issue in marketing strategy. This study aims to explore what kind of brand stories individuals prefer from the perspective of the level of self-construal and need of uniqueness. In this study, questionnaire survey is used to collect data in China. One way ANOVA and bootstrapping method of Process plug-in were adopted to test the hypotheses. This paper confirms that individuals with independent self-construal have higher need for uniqueness and prefer underdog brand story, while individuals with interdependent self-construal have lower need for uniqueness and prefer top dog brand story. This paper promotes the theoretical research in the fields of self-construal, need for uniqueness and brand story, and provides rich theoretical support for enterprises in designing, adjusting brand story. The implications, limitations and future studies are discussed.